2010
DOI: 10.1089/apc.2010.0086
|View full text |Cite
|
Sign up to set email alerts
|

From Access to Engagement: Measuring Retention in Outpatient HIV Clinical Care

Abstract: Engagement in HIV care is increasingly recognized as a crucial step in maximizing individual patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
241
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(247 citation statements)
references
References 26 publications
2
241
0
4
Order By: Relevance
“…Researchers have assessed retention in care in a number of different ways. [21][22][23][24][25] These measures have their own strengths and weaknesses, 26 but none of them takes into account the fact that frequency of attendance is related to changes in treatment and health status and may also be affected by external forces or changes in clinic policy. In the UK, for example, guidelines at the time the REACH study was conducted indicated that patients should be seen within 2-4 weeks of starting ART and every 3-6 months for routine monitoring on ART if they were considered 'stable', with good adherence and an undetectable viral load.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…Researchers have assessed retention in care in a number of different ways. [21][22][23][24][25] These measures have their own strengths and weaknesses, 26 but none of them takes into account the fact that frequency of attendance is related to changes in treatment and health status and may also be affected by external forces or changes in clinic policy. In the UK, for example, guidelines at the time the REACH study was conducted indicated that patients should be seen within 2-4 weeks of starting ART and every 3-6 months for routine monitoring on ART if they were considered 'stable', with good adherence and an undetectable viral load.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…This not only leads to poor clinical outcomes among such individuals but can also lead to the development of antiviral drug resistance and contribute to the ongoing spread of HIV in the community [23] [24]. Furthermore, since the initial ART regimen offers the best chance of viral suppression, immunologic recovery, and clinical stability, it is imperative that individuals be quickly integrated into a medical system that meets their needs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory data have been widely used as surrogate measures when data on primary care encounters are unavailable, as is often the case in large surveillance studies using public health laboratory data or cross-sectional population-based surveys that sample across defined geographic areas (e.g., county or state surveys). Such measures have been shown to be good indicators of initial or overall access to clinical HIV care (17), but there are no longitudinal data regarding concordance between measures of retention defined by HIV primary care encounters and those using surrogate laboratory measures (6,9,18,19).…”
mentioning
confidence: 99%